Learning to learn through networks of practices: Information literacy and exploitation of the territory with the project “Leggere tutti” - Cortiana, Paola (Formazione & insegnamento, 2022)
The article proposes a reflection on the European Key Competences "learning to learn" and "digital skills", through a broader path that aims at developing the values of citizenship set out in the plan for the introduction of civic education at school. In particular, as part of the project “Leggere tutti” promoted by the Education Department of the Municipality of Vicenza, activities are proposed for the knowledge and enhancement of the territory that pass through the development of the research methodology and critical thinking starting from reading. The activity, proposed to a pilot class in the school year 2021/22 provides for the construction of voices within the wikivoyage platform. The research focuses on the development, through this project, of the following dimensions: knowledge of the territory, research methodology, collaborative activity, writing skills.